2021
DOI: 10.1097/pts.0000000000000873
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Knowledge of Fall Prevention in Nurses Working in Acute Care Hospitals in China and the United States

Abstract: ObjectiveThe aim of the study was to investigate the perceived knowledge of fall prevention in nurses working in hospitals in China and the United States.MethodsA cross-sectional survey with 17 items was used to measure perceived knowledge of fall prevention of nurses working in hospitals in China and the United States.ResultsA total of 1442 nurses at 2 hospitals completed the survey in China (90% return rate), and 260 nurses in 2 hospitals in the United States (42% return rate) for a total sample size of 1702… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…According to knowledge about risk factors of falling among elderly, the findings of the present study indicated that most of them were aware of the risk of falling and mentioned that individuals who were weak in their lower extremities. This outcome in same line with study by (13) who conducted study about "The Perceived Knowledge of Fall Prevention in Nurses Working in Acute Care Hospitals in China and the United States" and indicated majority of the studied nurses had knowledge about risk factors among patients. Additionally, this finding is in line with the findings of a prior study by (14) , who investigated the "Knowledge among Nurses of Fall Prevention Hospital" and discovered that most participants were adequately informed about individuals who were at risk of falling, mentioned those who had lower extremity weakness, and mentioned that they were aware of the medications related to falls.…”
Section: Discussionsupporting
confidence: 86%
“…According to knowledge about risk factors of falling among elderly, the findings of the present study indicated that most of them were aware of the risk of falling and mentioned that individuals who were weak in their lower extremities. This outcome in same line with study by (13) who conducted study about "The Perceived Knowledge of Fall Prevention in Nurses Working in Acute Care Hospitals in China and the United States" and indicated majority of the studied nurses had knowledge about risk factors among patients. Additionally, this finding is in line with the findings of a prior study by (14) , who investigated the "Knowledge among Nurses of Fall Prevention Hospital" and discovered that most participants were adequately informed about individuals who were at risk of falling, mentioned those who had lower extremity weakness, and mentioned that they were aware of the medications related to falls.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, the hospital provided training opportunities to ensure consistent patient safety education. This finding is consistent with studies in Saudi Arabia, China, and the United States (Ganabathi, Mariappan & Mustafa, 2017;Wang et al, 2022). However, a previous study by Lim and Yam (2016) found a moderate level of knowledge among nurses.…”
Section: Total Mean Scoresupporting
confidence: 92%
“…The findings of the current study about senior people's knowledge of fall risk factors indicated that the majority of them were aware of the possibility of falling and mentioned having a weakness in their lower limbs. This outcome in sаme line with study by Wаng, et аl., who conducted study аbout "The Perceived Knowledge of Fаll Prevention in Nurses Working in Аcute Cаre Hospitаls in Chinа аnd the United Stаtes" and indicated majority of the studied nurses had knowledge about risk factors among patients [35]. Furthermore, this outcome aligns with the findings of a prior investigation by Gupta, who carried out research regarding "Knowledge аmong nurses of fаll prevention hospitаl" аnd showed thаt mаjority of the studied hаd аdequаte knowledge аbout at risk of falling and mention that those they have a weakness of the lower extremities, mention that they know the medications associated with falls [36].…”
Section: Discussionmentioning
confidence: 99%